Halal bi halal in the month of Shawwal in view of the rule "Al'aadah Muhakkamah" (traditions became basic of law) - , Bikodarin; , Dr. Imron Rosyadi.,M.Ag; , Dr. Muthoifin. M.Ag (2017)
Being a matter that has been advised that in Indonesia there are many customs are done by Muslims, one of them is Halal bi Halal wich is held in the month of Shawwal. In this simple thesis, is focused explained and described the customs of this in terms of whether or not the law should hold such customs, with the aim of: a. In order to be known to the law held a halal bi halal is done in the midst of society in view of the Islamic Shari'a b. Apply the rule "Al'aadah Muhakkamah" (Tradition was basic of law) in held Halal bi Halal by explaining the limitations permissibility c. Explaining to the Muslim community about the nature of these laws, and restrictions are allowed to hold it by quoting the opinion of scholars Indonesia about Halal bi Halal in the month of Shawwal, either allow it or ban it or moderate (not allow and does not forbid), so that people can choose opinion of most rojih (strong) by them. In order to realize these objectives, the use of applied analytical methods, research methods proposition and method description. By explaining the meaning of the rules in language or in terms syar'i, outlining the elements and explain the meaning of the sentence contained in it, and look for the basic proposition that becomes a reference of the rule and examine the rule "Al'aadah Muhakkamah" (Tradition became basic of law) to serve as a legal proposition held Halal bi Halal in the month of Shawwal. Then amplifies these rules with other arguments relating of the Qur'an and Sunnah. After the analysis and assessment of the arguments relating, finally concluded the following: a. Halal bi halal in the month of Shawwal including new tradition that have not been known at the time of the Prophet Muhammad, his companions and the tabi'in. However, Halal bi Halal held in the month of Shawwal not violate the values of the Qur'an and Sunnah. b. Opinions which allow held Halal bi Halal in the month of Shawwal is not opinion based on the wishes of lust, but the majority opinion of some of the greatest scholars Indonesian Islamic organizations.